Toying with the periodic table: using everyday items to investigate classification and properties of matter. (1st October 2020) - Bergman, Daniel
Abstract: The Periodic Table of Elements is a valuable resource for chemists and all kinds of STEM professionals. However, it can be initially overwhelming and intimidating to some students. This hands-on lesson introduces abstract concepts in the periodic table through a tangible experience with simple toys and household objects. Students collaborate and think critically to explore different ways for classifying and categorizing matter. This experience of analyzing traits and recognizing trends in properties provides an orientation to the periodic table's development and organization of chemical elements. Extension options and instructional methods are provided, and are adaptable to fit teachers' curriculum and classroom context.